Why Peritoneal Dialysis is Underutilized in the United States: A Review of Inequities - Bassuner, Juri; Kowalczyk, Bridget; Abdel-Aal, Ahmed Kamel (Seminars in Interventional Radiology, 2022)
Given a choice, most patients with end-stage renal disease prefer home dialysis over in-center hemodialysis (HD). Peritoneal dialysis (PD) is a home dialysis method and offers benefits such as absence of central venous access and therefore preservation of veins, low cost, and decreased time per dialysis session, as well as convenience. Survival rate for patients on PD has increased to levels comparable to in-center HD. Despite endorsement by leaders in the medical field, professional societies, and those in government, PD has reached only 11% adoption among incident patients according to the 2019 United States Renal Data System Annual Data Report. This figure is dwarfed in comparison to rates as high as 79% in other countries. In addition, research has shown that inequities exist in PD access, which are most pronounced in rural, minority, and low-income regions as demonstrated by trends in regional PD supplies. To complicate things further, technique failure has been implicated as a major determinant of poor PD retention rates. The low initiation and retention rates of PD in the United States points to barriers within the healthcare system, many of which are in the early phases of being addressed.
Keywords: peritoneal dialysis; end-stage renal disease; hemodialysis; inequities; interventional radiology